Perancangan Media Interaktif Gerak Tari Topeng Patih pada Wayang Topeng Malangan Menggunakan Sensor Kinect - Bayu Ramadhani Fajri; Agariadne Dwinggo Samala; Fadhli Ranuharja (Universitas Negeri Padang, 2020)
Tari Topeng Patih is a part of the traditional dance performance art “Wayang Topeng Malangan” with a religious background which grew up around people in Malang City, East Java. Presently, art gallery of Tari Topeng Malangan has been difficult to be found. In addition to the difficulty of finding this art gallery even in the regions of origin, the problems is also about the interest and enthusiastic public, especially teenagers in Malang to learn this dance is still very rare. As a result, this art is slowly deteriorated and increasingly falling by the presence of various modern performances. In regarded to learn Tari Topeng Patih, the conventional learning activities requiring a special place such as a dance studio that is generally located far away from downtown Malang. Thus to overcome this problem is requires an instructional media that can be used as an alternative solution to learn and obtain information about Tari Topeng Patih, one way may be able to use the simulation method by utilizing the technology and education. The results of the design is the interactive media learning and simulation for basic motion of Tari Topeng Patih by using Kinect media.